Surveillance of Drinking Water Quality Worldwide: Scoping Review Protocol - Lopes, Rayssa Horacio; Silva, Cícera Renata Diniz Vieira; Salvador, Pétala Tuani Cândido de Oliveira; Silva, Ísis de Siqueira; Heller, Léo; Uchôa, Severina Alice da Costa (International journal of environmental research and public health, 2022)
Universal access to clean and safe drinking water is essential for life maintenance since exposure to poor quality water is harmful to health. Drinking water quality is part of public health actions and, together with sanitation, a human right essential for life and a sustainable development goal. Moreover, an independent surveillance system conducted by the Ministry of Health or government agencies is needed for the safety of drinking water quality. We propose a scoping review protocol to identify and map worldwide surveillance actions and initiatives of drinking water quality implemented by government agencies or public health services. This scoping review protocol is based on the Joanna Briggs Institute manual and guided by the PRISMA-ScR. Articles, theses, dissertations, and official documents consulted in the following databases will be included: Medline/PubMed, Scopus, LILACS, Web of Science, Embase, Engineering Village, and gray literature. No date limit or language will be determined. The authors will develop a worksheet for data extraction. Quantitative (simple descriptive statistics) and qualitative data (thematic analysis) will be analyzed. The final scoping review will present the main findings, impacts, challenges, limitations, and possible research gaps related to surveillance of drinking water quality on population health.